2014
DOI: 10.1177/0194599814545083
|View full text |Cite
|
Sign up to set email alerts
|

Matrix‐Metalloproteinases in Head and Neck Carcinoma–Cancer Genome Atlas Analysis and Fluorescence Imaging in Mice

Abstract: Objective (1) Obtain matrix-metalloproteinase (MMP) expression profiles for head and neck squamous cell carcinoma (HNSCC) specimens from the Cancer Genomic Atlas (TCGA). (2) Demonstrate HNSCC imaging using MMP-cleavable, fluorescently labeled ratiometric activatable cell-penetrating peptide (RACPP). Study Design Retrospective human cohort study; prospective animal study. Setting Translational research laboratory. Subjects and Methods Patient clinical data and mRNA expression levels of MMP genes were down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 29 publications
4
29
0
Order By: Relevance
“…In addition, MMP14 also plays a key role in potentiating cancer cell migration [32, 33]. These results are in agreement with recent findings, which indicate a poor 5-year survival rate in patients with increased MMP14 expression regardless of HPV status and make it a potential target since its selective inhibition blocked tumour growth, invasion and angiogenesis [34, 35]. …”
Section: Discussionsupporting
confidence: 86%
“…In addition, MMP14 also plays a key role in potentiating cancer cell migration [32, 33]. These results are in agreement with recent findings, which indicate a poor 5-year survival rate in patients with increased MMP14 expression regardless of HPV status and make it a potential target since its selective inhibition blocked tumour growth, invasion and angiogenesis [34, 35]. …”
Section: Discussionsupporting
confidence: 86%
“…The release of model drug Cy3 will result in decrease of FRET intensity that can be investigated via cell lysis using fluorescence spectrometry. According to the previous reports [4446], the ratio, I Cy3 /I FRET , was calculated to quantify the FRET change, where I Cy3 and I FRET are the fluorescence intensity at 562 nm and 664 nm, respectively (excitation 520 nm). For the conjugate P-Cy3-Cy5, the ratio in medium alone was 2.35, and in initial stock was 1.97.…”
Section: Resultsmentioning
confidence: 99%
“…However, the currently available tools to identify dysplasia, such as toluidine blue and endogenous tissue fluorescence detection, demonstrate high false-positivity and the inability to distinguish high-risk from low-risk lesions [2933]. Intravenous fluorescent-labeled targeting agents, based on protoporphyrin precursors [34], antibodies [35] and enzyme-activatable peptides [36], represent a promising strategy to deliver accurate, high-contrast identification of tumor with minimal side effects. However, there is limited study of these agents within the context of dysplasia [3739]; only one other agent besides our present study has been reported in a model of oral dysplasia [40].…”
Section: Discussionmentioning
confidence: 99%